Emerging Private Education in Pakistan administrative Kashmir and Determinants of households Choice Public versus Private Schooling - Shabbir, Muhammad (Advances in Social Sciences Research Journal, 2015)
The number of private schools has been increased since decentralization of education in Pakistan as well as in Azad Jammu & Kashmir. Annual Status of Education Report (ASER) and a random sampling survey of 103 households of all income groups from ditrist Kotli AJ&K Pakistan was made for analysis. With the help of ASER report 2011-2014 we observed that number of private schools has increased whereas number of public schools declined. Moreover we applied binary regression to find out the factor which affected the parent’s decision towards the school choice for their children. We used household choice dichotomous dependent variable (type of school ) whereas family characteristics, child characteristics and school characteristics as independent variables which are sub categorized into, , father & mother education level, household per capita income, family size, child gender & education level, school cost, school medium of instruction , school distance from household and quality of education which has been observed as one of the most effective determinants of school choice in state of Azad Jammu & Kashmir rural.